EXPERIMENTAL DATA ON THE CHOICE OF THE THEME FOR BACHELOR'S THESIS BY STUDENTS - DENISA ADRIANA MANEA; CRISTIAN STAN (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. Development of the bachelor's thesis is one of the most important and representative moments of a student's academic progress. In fact, the graduation bachelor's thesis indicates the written expression and synbachelor's thesis of knowledge, skills and research abilities acquired during the years of study. However, there are relatively few studies that address this issue in an empirical manner. Considering this fact, this article focuses on identifying the main factors guiding the student in choosing a specific theme for the bachelor's thesis, the steps taken and time spent to develop it and the issues on which the graduate is focused upon during the presentation. Based on the interpretation of the collected data, a set of conclusions is formulated aimed at identifying opportunities to optimize the coordination activity of the theses.